A facile and green approach toward precise fabrication of silk fibroin-based microfluidic devices using water as etchant. (5th October 2022) - Zhou, Mengyuan; Wu, Shiming; Song, Fangmiao; Chen, Feng; Wang, Feng; Xia, Qingyou; Sun, Wei; Wang, Chenhui; Qiao, Yan; Yu, Ling; Lu, Zhisong
Graphical abstract: A tape-mask-assisted water-etching technique was developed to precisely prepare silk fibroin-based microchannels with hydrogel surface layers, which could facilitate cell adhesion and growth for creating a microvessel-like structure. Highlights: A water-etching technique was developed to prepare RSF-based microfluidic devices. The pattern of RSF-based microfluidic devices could be precisely tailored. A hydrogel surface layer was formed on the RSF channel to facilitate cell adhesion and growth. RSF-based biomimetic vascular channels could be simply fabricated. Abstract: Regenerated silk fibroin (RSF) is considered as a superior substrate material for biocompatible and biodegradable microfluidic devices. However, the manufacture of RSF-based microfluidic chips in a simple, low-cost, and environmentally friendly manner remains a difficulty. We devised a tape mask-assisted approach for preparing RSF-based microfluidic chips for cell adhesion and growth utilizing water as an eco-friendly etchant. The RSF solution was pre-hydrolyzed to assure the RSF film's water-solubility. The UV–visible spectra reveal that the RSF film, as made, is easily dissolved in water. The film could be turned into a water-insoluble state after being treated with ethanol for 40 min. Concave and convex micro-patterns may be formed on the RSF film using tape mask-assisted water etching and ethanol-induced insolubilization. Controlling the etching period allowed the tape-mask designs to be carefully transferred to the RSF film. Unlike LiBr etching, water treatment creates channels that are covered by a smooth RSF hydrogel layer, which may aid cell adhesion and development. The creation of the hydrogel layer might be explained by the insoluble RSF chains exposed after water etching and the ethanol-induced conformation change. Human umbilical vein endothelial cells were seeded in a blood vessel-like RSF-based channel, demonstrating the quick attachment and growth tendency. After 7 days of growth, a micro-vessel-like structure was visible in the channel, suggesting the device's high biocompatibility and vast potential. This work introduces a low-cost, facile and eco-friendly approach to fabricating RSF-based microfluidic devices for cell- or tissue-based assays.